Effectiveness and Safety of Intravitreal Brolucizumab for Diabetic Macular Edema After Vitrectomy: A Before-and-After Study at a Specialized Center in Japan - Saito K; Akiyama H (Clinical Ophthalmology)
Kazuma Saito, Hideo Akiyama Department of Ophthalmology, Gunma University Graduate School of Medicine, Gunma, 371-8511, JapanCorrespondence: Kazuma Saito, Department of Ophthalmology, Gunma University Graduate School of Medicine, 3-39-15 Showa-machi, Maebashi, Gunma, 371-8511, Japan, Tel +81-27-220-8338, Fax +81-27-220-3841, Email kazuma3110@gunma-u.ac.jpPurpose: To evaluate the efficacy and safety of intravitreal brolucizumab (IVBr), a vascular endothelial growth factor inhibitor, for injections in vitrectomized eyes with diabetic macular edema (DME) over 1 year.Patients and Methods: This retrospective before-and-after study analyzed 23 eyes of 20 patients with DME after vitrectomy. Outcomes assessed over 1 year included best-corrected visual acuity (BCVA), central subfield retinal thickness (CST), and the number of IVBr injections administered. The treatment protocol consisted of an initial IVBr injection followed by a pro re nata regimen. If CST did not improve after the last IVBr injection, treatment was switched to intravitreal triamcinolone acetonide injection (IVTA), sub-Tenon’s triamcinolone acetonide (STTA) injection, or intravitreal faricimab (IVFa).Results: Seven eyes (30.4%) completed one-year IVBr treatment. There was no significant change in BCVA during the treatment period (LogMAR BCVA [mean±standard error]: baseline, 0.44± 0.10; 6 months, 0.35± 0.12 [P=0.22]; at 1 year, 0.37± 0.11 [P=0.24]). However, CST (mean±standard error) significantly improved from baseline (558± 36.3 μm) to 6 months (338± 27.1 μm [P< 0.05]) and 1 year (307± 20.4 μm [P< 0.05]). The mean number of IVBr injections was 3.6± 1.3 (mean±standard deviation). Of the 16 eyes (69.6%) from 14 patients who did not complete one-year IVBr treatment, 11 eyes showed no CST improvement following the last IVBr injection, prompting a switch to IVTA, STTA, or IVFa in seven, one, or three eyes, respectively. Additionally, IVBr treatment was discontinued in one eye due to intraocular inflammation, while four patients (four eyes) dropped out within 1 year after starting treatment.Conclusion: Our findings demonstrated partial efficacy of IVBr in managing DME in vitrectomized eyes. However, variable responses often necessitate supplementary treatments to achieve therapeutic goals.Keywords: anti-vascular endothelial growth factor, diabetes, intraretinal edema, vitrectomy, best-corrected visual acuity, central subfield retinal thickness